2021
DOI: 10.3390/electronics10222839
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Control of Centralized Thermoelectric Generation System under Nonuniform Temperature Distribution Using Barnacles Mating Optimization Algorithm

Abstract: The need for renewable energy resources is ever-increasing due to the concern for environmental issues associated with fossil fuels. Low-cost high-power-density manufacturing techniques for the thermoelectric generators (TEG) have added to the technoeconomic feasibility of the TEG systems as an effective power generation system in heat recovery, cooling, electricity, and engine-efficiency applications. The environment-dependent factors such as the nonuniform distribution of heat, damage to the heat-transfer co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…A survey utilized the barnacle mating optimization (BMO) algorithm for optimal MPPT control of TEG systems under NTD conditions (Tariq et al, 2021). Comparing the results with the GWO, PSO, and cuckoo search (CS) algorithms, it was found that the proposed BMO algorithm provides good grid connectivity with minimal oscillations and minimal transient fluctuations in output voltage.…”
Section: Barnacles Mating Optimization Algorithm For Tegmentioning
confidence: 99%
“…A survey utilized the barnacle mating optimization (BMO) algorithm for optimal MPPT control of TEG systems under NTD conditions (Tariq et al, 2021). Comparing the results with the GWO, PSO, and cuckoo search (CS) algorithms, it was found that the proposed BMO algorithm provides good grid connectivity with minimal oscillations and minimal transient fluctuations in output voltage.…”
Section: Barnacles Mating Optimization Algorithm For Tegmentioning
confidence: 99%